Review Of Factors In Business Type Selection Study On Kbmi Participating Students - Hartono Hartono; Budhi Adhiani Christina; Rif’ah Dwi Astuti; Sugiyanta Sugiyanta; Makmun Riyanto (International Journal of Business and Quality Research, 2023)
The Indonesian government is serious about preparing new entrepreneurs from the higher education sector. The Indonesian Student Business Competition (KBMI) program is the answer to the need for Start-Up Businesses in Indonesia. This study examines the implementation model of the KBMI Program by developing three hypotheses from the relationship between the variables of experience factor, education factor, and other factors. This study uses 90 respondents from KBMI Program students in 50 universities in Indonesia. SPSS was chosen to test the model and hypotheses of this study. The results showed that all hypotheses proposed were accepted, with the experience variable being the most dominant in this model. This proves that experience is the key to the success of the KBMI Program. The practice of becoming a Start-Up Business is the right step in building the willingness and ability to become a Start-Up Business after graduating from higher education.